2016
DOI: 10.1111/jnc.13666
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure impairs function and expression of breast cancer‐resistant protein (BCRP) at rat blood–brain barrier partly via ammonia‐ROSERK1/2 activation

Abstract: We once reported that P-glycoprotein (P-GP) and multidrug resistance-associated protein 2 (MRP2) were oppositely regulated at the blood-brain barrier (BBB) of thioacetamideinduced acute liver failure (ALF) rats. This study aimed to investigate whether ALF affected function and expression of breast cancer-resistant protein (BCRP) at the BBB of rats and the role of ammonia in the regulation. ALF rats were developed by intraperitoneal (i.p.) injection of thioacetamide (300 mg/kg) for 2 days. Hyperammonemic rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 50 publications
3
38
0
Order By: Relevance
“…Acute hepatic failure is associated with hyperammonaemia, which in turn is associated with neuroinflammation and neuropsychiatric presentations, such as hepatic encephalopathy (Albrecht and Norenberg, 2006;Ott and Vilstrup, Australian & New Zealand Journal of Psychiatry, 52(10) 2014). The ammonia crosses into BMECs, where it adversely affects the functioning and expression of breast cancer resistance protein (BCRP) by activation of ammonia-ROS-extracellular-regulated protein kinase-1/2 (ERK1/2) (Li et al, 2016c). Murine experimentation has recently shown that NAC (a ROS scavenger) restores the functioning and expression of BCRP (Li et al, 2016c).…”
Section: N-acetylcysteinementioning
confidence: 99%
See 1 more Smart Citation
“…Acute hepatic failure is associated with hyperammonaemia, which in turn is associated with neuroinflammation and neuropsychiatric presentations, such as hepatic encephalopathy (Albrecht and Norenberg, 2006;Ott and Vilstrup, Australian & New Zealand Journal of Psychiatry, 52(10) 2014). The ammonia crosses into BMECs, where it adversely affects the functioning and expression of breast cancer resistance protein (BCRP) by activation of ammonia-ROS-extracellular-regulated protein kinase-1/2 (ERK1/2) (Li et al, 2016c). Murine experimentation has recently shown that NAC (a ROS scavenger) restores the functioning and expression of BCRP (Li et al, 2016c).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…The ammonia crosses into BMECs, where it adversely affects the functioning and expression of breast cancer resistance protein (BCRP) by activation of ammonia-ROS-extracellular-regulated protein kinase-1/2 (ERK1/2) (Li et al, 2016c). Murine experimentation has recently shown that NAC (a ROS scavenger) restores the functioning and expression of BCRP (Li et al, 2016c).…”
Section: N-acetylcysteinementioning
confidence: 99%
“…NF-κB activation was found responsible for transporter upregulation. Further, another recent report from the same group, concluded that ROS mediated ERK1/2 phosphorylation was involved in the downregulating BCRP expression in rat BBB [ 72 ].…”
Section: Oxidative Stress Regulates Abc Transportersmentioning
confidence: 99%
“…Our previous studies have verified that hyperammonemia increases the function and expression of P-gp at the bloodbrain barrier by activating the NF-κB pathway [35] and that ALF impairs the function and expression of BCRP at the bloodbrain barrier partly by activating the ammonia-ROS-ERK1/2 pathway [23] . These results indicate tissue-specific alterations in the expression and function of P-gp and BCRP in ALF rats.…”
Section: Discussionmentioning
confidence: 86%
“…These membranes act as defenders against numerous exogenous and endogenous substances. Our previous study has also indicated that acute liver failure (ALF) impairs the function and expression of P-gp and BCRP at the blood-brain barrier in rats, thus resulting in increased brain distributions of rhodamine 123 and prazosin [23,24] . However, information on intestinal P-gp and BCRP functions and expression under liver failure status is lacking.…”
Section: Introductionmentioning
confidence: 99%